PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PERUSAHAAN PADA PT SINAR MAS AGRO RESOURCES AND TECHNOLOGY, TBK PERIODE 2013-2024 - Hasanah, Ismiyatun; Krisnaldy, Krisnaldy (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the partial and simultameous effects of Liquidity and Profitability on Capital Structure at PT Sinar Mas Agro Resources and Technology Tbk during the period of 2013-2024. The research employs a quantitative method using secondary data in the form of the company’s annual financial statements. The data analysis techniques used include descriptive analysis, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, as well as hypothesis testing using the t-test and F-test, processed with SPSS version 27. The partial test results show that Liquidity, as proxied by Current Ratio (CR), has a significant effect on Capital Structure (DER), with a t-value of -3,847, which is greater than the t-table value (2,26216), and a significance value of 0,004 < 0,05. In contrast, Profitability, measured by the Net Profit Margin (NPM), does not show a significant effect on Capital Structure, with a t-value of -0,128 < t-table (2,26216), a significance value of 0,901 > 0,05, and a t-table value greater than the calculated value. Simultaneously, the F-test results show that Liquidity and Profitability together have a significant effect on Capital Structure, with an F-value of 7,553,ngreater than the F-table value (4,26), and a significance value of 0,012 < 0,05. The coefficient of determination (R2) is 75,53%, which means that the two independent variables contribute 75,53% to the variation in Capital Structure. The remaining 24,47% is influenced by other factors not included in this study.